New Developments in the Theory of the Historical Process : Polish Contributions to Non-Marxian Historical Materialism - Brzechczyn, Krzysztof (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2022)
The first part of this book contains a selection of Leszek Nowak's (1943-2009) works on non-Marxian historical materialism, which are published here in English for the first time. In these papers, Nowak constructs a dynamic model of religious community, reconstructs historiosophical assumptions of liberalism and considers the methodological status of prognosis of totalitarization of capitalist society. In the second part of the book, new contributions to non-Marxian historical materialism are presented. Their authors analyze mechanisms of the oligarchization of liberal democracy, the democratization of real socialism, and the development of early modern Ottoman and post-war Chinese societies.